2022
DOI: 10.56261/jars.v20i1.249299
|View full text |Cite
|
Sign up to set email alerts
|

A Review Article: Fall Incidents and Interior Architecture— Influence of Executive Function in Normal Ageing

Abstract: Many ageing people are staying at home, whether they are self-isolating or social distancing, because of the current Covid-19 situation. Fall incidents at home among the ageing are significantly associated with a high level of mortality. Bathrooms are frequently reported as a major environmental hazard in connection with falls. This serious health risk raises the matter of interior architecture. In terms of preventing falls, more architectural research focuses on interior elements e.g., handrail design, and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Attention and decision-making with respect to physical interventions are linked to cognitive function and performance. Past studies reported that attention and decision-making interventions contribute to cognitive health as well as to successful ageing (Chanbenjapipu et al, 2023;Chuangchai & Siripakarn, 2019;Kelly, 2020).…”
Section: Physical Environment Interventionmentioning
confidence: 99%
See 4 more Smart Citations
“…Attention and decision-making with respect to physical interventions are linked to cognitive function and performance. Past studies reported that attention and decision-making interventions contribute to cognitive health as well as to successful ageing (Chanbenjapipu et al, 2023;Chuangchai & Siripakarn, 2019;Kelly, 2020).…”
Section: Physical Environment Interventionmentioning
confidence: 99%
“…The ball juggling is correlated to motor coordination, which relies on motor function and performance (Haibach, Daniels, & Newell, 2004). Ageing persons commonly experience a degeneration of motor performance (Chanbenjapipu et al, 2023). Unsurprisingly, ageing persons have slower movement speed and are less smooth in motor performance than younger people since motor performance remains naturally stable throughout young adulthood and diminishes in late adulthood (Boyke, Driemeyer, Gaser, Büchel, & May, 2008;Moustafa, 2014).…”
Section: Juggling Balls Testmentioning
confidence: 99%
See 3 more Smart Citations